Vibration analysis of unbalanced and misaligned rotor system using laser vibrometer - Masrol, Shaiful Rizal; Madlan, M.A.; Md Salleh, Salihatun; Ismon, Maznan; Roslan, Mohd Nazrul (Trans Tech Publications, 2013)
Rotor unbalance and shaft misalignment are common major concerns in rotating system. In this study, vibration analysis for unbalanced rotor and misaligned shaft components using non-contact laser Doppler vibrometer (LDV) were examined. The vibration acceleration magnitude (m/s2) and FFT spectrum from the both fault detections were recorded by the portable laser Doppler vibrometer and analysed by the vibration analysis software. The result shows that combination of unbalance and parallel misalignment fault conditions can produce higher vibration thus reduce the life span of the rotor system. In this case, the unbalance fault condition combined with parallel misaligned rotor gave highest vibration magnitude followed by simply unbalanced rotor and parallel misalignment fault only. This experiment shows that the non-contact method has successfully detected the unbalance and parallel misalignment fault in the rotor system.